2010
DOI: 10.1093/ndt/gfq608
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of chronic kidney disease: a population study in the Tibetan population

Abstract: This is the first population-based epidemiological study of CKD in the Tibetan population. We found a higher prevalence of CKD and associated high prevalence of albuminuria, hypertension, hyperuricaemia and high haematocrit in the Tibetan population. The present study indicates the urgent need to develop comprehensive strategies targeted at reducing the CKD burden in this area and may lead to a better understanding of CKD in high-altitude populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 25 publications
10
63
0
1
Order By: Relevance
“…47 A large epidemiologic study in Tibet also found a significant increased prevalence of hyperuricemia in Tibetans compared with prior studies performed among Han Chinese people living in Guangzhou. 46 Moreover, subjects living at high altitude also have a low fractional excretion of uric acid despite the high serum levels of uric acid 47 ; similar findings have been described in congenital cyanotic heart disease. 65 Interestingly, the higher prevalence of hyperuricemia associates with both the presence of microalbuminuria and systemic hypertension.…”
Section: Hyperuricemia and Hypertensionmentioning
confidence: 61%
See 4 more Smart Citations
“…47 A large epidemiologic study in Tibet also found a significant increased prevalence of hyperuricemia in Tibetans compared with prior studies performed among Han Chinese people living in Guangzhou. 46 Moreover, subjects living at high altitude also have a low fractional excretion of uric acid despite the high serum levels of uric acid 47 ; similar findings have been described in congenital cyanotic heart disease. 65 Interestingly, the higher prevalence of hyperuricemia associates with both the presence of microalbuminuria and systemic hypertension.…”
Section: Hyperuricemia and Hypertensionmentioning
confidence: 61%
“…65 Interestingly, the higher prevalence of hyperuricemia associates with both the presence of microalbuminuria and systemic hypertension. 46 For example, in our study of Tibetans, 38% of subjects had hypertension, 29% had hyperuricemia, and 16% had albuminuria (including microalbuminuria). However, reduced GFR (defined as estimated GFR Ͻ60 ml/min per 1.73 m 2 ) was observed in only 2% of these subjects.…”
Section: Hyperuricemia and Hypertensionmentioning
confidence: 64%
See 3 more Smart Citations